2023
DOI: 10.1038/s41418-023-01118-z
|View full text |Cite
|
Sign up to set email alerts
|

The regulation loop of MARVELD1 interacting with PARP1 in DNA damage response maintains genome stability and promotes therapy resistance of cancer cells

Abstract: The DNA damage response (DDR) plays crucial roles in cancer prevention and therapy. Poly(ADP-ribose) polymerase 1 (PARP1) mediates multiple signal transduction in the DDR as a master regulator. Uncovering the regulatory factors of PARP1 contributes to a more comprehensive view of tumorigenesis and treatment strategies. Here, we reveal that MARVELD1 acts as a mediator of DDR to perform early events and maintain genome stability. Mechanistically, PARP1 PARylates MARVELD1 at D102, D118 and D130, and in turn, MARV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…MARVELD1, a member of the MARVEL domain-containing protein family, exhibits tumor suppressor activity in breast, cervical, prostate, hepatocellular, and other cancers (34)(35)(36). Previously, a basic study demonstrated MARVELD1's role in inducing resistance to 5-FU combined with olaparib in colorectal cancer (37). yet its function in ovarian cancer has remained underexplored.…”
Section: Discussionmentioning
confidence: 99%
“…MARVELD1, a member of the MARVEL domain-containing protein family, exhibits tumor suppressor activity in breast, cervical, prostate, hepatocellular, and other cancers (34)(35)(36). Previously, a basic study demonstrated MARVELD1's role in inducing resistance to 5-FU combined with olaparib in colorectal cancer (37). yet its function in ovarian cancer has remained underexplored.…”
Section: Discussionmentioning
confidence: 99%
“…Staining was visualized with DAB and hematoxylin counterstaining. For semi-quantitative analysis, two pathologists independently evaluated the stained sections according to evaluation standards on a 12-point scale by calculating the immunoreactivity score [ 62 ]. For IHC staining of mice tumor tissues following standardized procedures, the primary antibodies used were anti-CD4 (67786-1-lg, Proteintech) and anti-CD8 (29896-1-AP, Proteintech).…”
Section: Methodsmentioning
confidence: 99%